IInvestigation, Structural Characterization and Evaluation of the Biological Potency by Molecular Docking of Amoxicillin Analogue of a Schiff Base Molecule - Tahiroğlu, Veysel; Gören, Kenan; Yildiko, Umit; Bağlan, Mehmet (My University, 2024)
We describe the Theoretical Chemical Calculations of the amoxicillin-based Schiff base generated by the interaction of the antibiotic amoxicillin with 2,6-diaminopyridine in this work. The Gaussian09 software program was used for this. Quantum chemical calculations of the compound (molecular geometry, geometric structure, optimized geometric parameters, bond angle and bond length) have been carried out using SDD and 6-311G basis sets and density functional theory (DFT/ B3LYP) and (DFT/B3PW91) tehniques. The HOMO-LUMO energies of our compound were determined utilizing the DFT method with two methods and basis sets. The compound's molecular electrostatic potential (MEP) surface, NBO analysis, Nonlinear Optical Properties (NLO), Mulliken atomic charges have been calculated using two methods and sets. In the last phase of this study, the compound was subjected to molecular docking studies for enzyme inhibition. Furthermore, homology modeling and molecular docking analysis have been done to assess the biological and medical aspects of this ligand by measuring the attraction intensity and attraction energies of molecular ligand-biological contact complexes.
Keywords: MEP; DFT; 2; Schiff Base; Molecular Docking.; NBO. Amoxicillin; 6?Diaminopyridine